Analisis Kemampuan Siswa Berdasarkan Gaya Bahasa dan Intelegensi dalam Menentukan Unsur Intrinsik Teks Bacaan Cerita Anak - Tarigas, Wina Kristin; Halidjah, Siti; Salimi, Asmayani; Suparjan, Suparjan; Pranata, Rio (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This study aims to analyze students' ability to determine the intrinsic elements of children's story texts. This study used the descriptive qualitative method. It involved the fourth-grade students at State Elementary School 30 South Pontianak with a total o 22 students. Data were collected from a multiple-choice test consisting of 40 questions. Data were analyzed with 4 stages of data collection, data reduction, data presentation, and drawing conclusions. The results showed that the student’s average ability to determine intrinsic elements in children's story texts was 75.8 with a good category. Furthermore, 6 students (0.27%), 9 students (0.42%), and 7 students (0.31%) respectively showed very good, good, and sufficient categories in determining the intrinsic elements of the children’s story text. It can be concluded that some students still have difficulties in determining the intrinsic elements of children’s story texts.